The Naik Ayun Tradition Among the Bugis Community in Peniti Dalam II Village, Segedong District, Mempawah Regency - Nuripansyah, Nanang; Rustiyarso, Rustiyarso; Putri, Astrini Eka (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
The Bugis community of Peniti Dalam II Village has a custom called naik ayun or menre tojang. Menre tojang comes from the Bugis language; menre means to rise or to climb, while tojang means swing or a device for swinging. This study uses a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. Based on the research results, the Bugis community of Peniti Dalam II Village generally still carries out the naik ayun ceremony, but some of its practices are no longer entirely in accordance with the original traditions they used to follow. The cause is changes in the implementation, both in terms of the process and the tools and equipment used. The Bugis community of Peniti Dalam II Village continues to strive to preserve the naik ayun traditional ceremony in several ways, including continuing to perform it, involving and teaching it to their descendants, and publicizing it during every traditional event through mass media.